Orodja za odzivanje na poplave - Struc, Nežka (Etnolog. Nova vrsta (Ljubljana), 2025)
In this article we analyse tools designed for preparedness and response to various crises and natural disasters. The analysis was carried out as part of the international Sonar-Cities project, and helped to identify the characteristics of similar tools in various European countries. In this text, we analyse Slovenian tools for responding to floods and other disasters. Among other things, we break down how the tools address vulnerabilities in the context of the health consequences of disasters and to what extent they promote solidarity and mutual assistance in Ljubljana neighbourhoods.
Keywords: cultural anthropology; ethnology; etnologija; floods; health; kulturna antropologija; naravne nesreče; natural disasters; orodja; poplave; ranljivost; solidarity; solidarnost; tools; vulnerability; zdravje